MUVE: A Long-Term Science Museum-Based Environmental Volunteer Conservation Program. - Jones, Shannon C.; Reilly, Lauren; Bretos, Fernando; Freund, Cathryn A. (Journal of Museum Education, 2024)
Science museums and similar institutions provide informal science and environmental education, both on museum grounds and out in the community. Since 2007, the Phillip and Patricia Frost Museum of Science in Miami, Florida, USA, has run Museum Volunteers for the Environment (MUVE) program, a conservation volunteer program that is also an effective method of place-based education for the local community. Here, we document the evolution of MUVE over the past 15 years, from a small eco-art installation to a multi-faceted conservation program that brings the museum into nature, and share the program's recent achievements. We outline program activities, participation, funding sources, key challenges, and lessons learned. Our goal in doing so is to provide a case study to other museums interested in developing similar programs.